Poly(ether ether ketone)s containing benzene pendant in the molecular chain: Synthesis, characterization and optical properties. (June 2021) - Chen, Yan; Ren, Fajian; Dai, Jian gang; Li, Dongmei; Luo, Shajie
A series of modified poly(ether ether ketone)s containing different content of benzene pendant group in the molecular chain have been successfully synthesized with 1, 1-bis(4-hydroxyphenyl)-1-phenylethane, bisphenol A and 4, 4′-difluorobenzophenone by nucleophilic substitution. The inherent viscosities of obtained polymers were in the range of 0.261–0.889 dLg −1 . They were found to have high glass transition temperatures (Tg ) of 150–168°C and 148–169°C (examined by DSC and DMA, respectively), good thermal stability with 5% weight-loss temperature (T5% ) of 439–469°C. The tensile strengths of the obtained polymers were 67.7–86.6 MPa, and the storage modulus was over 0.9 GPa at about 140°C. The modified poly(ether ether ketone)s showed the excellent solubility property, they could be processed by solution method. Additionally, the obtained polymers had good optical transmittance (>70%) at 400 nm, suggesting that they have potential to be applied to the heat-resistant optical films.